1986
DOI: 10.1007/bf01144715
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical aspects of calcium vanadate apatite

Abstract: By appropriate modifications of existing precipitation methods, a sample of calcium vanadate apatite, Cal0(VO4)e(OH)2 was prepared at 11 0 ° C. It was characterized through X-ray, electron microscopic, infrared and thermoanalytical analyses in addition to chemical analysis. Equilibrating the sample in buffered aqueous media at 37 ° C, the solubility was measured using microanalytical techniques of Ca 2+ and VO 3-present in the saturated solutions after separating the colloidal component of the solute. Duration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…In all recorded ATR-FT-IR spectra ( Figure 4 a–c), bands originating from the phosphate (PO 4 3− ), vanadate (VO 4 3− ) and hydroxyl (OH − ) groups are present. Their locations are consistent with the data available in the literature and confirm that the materials have the hexagonal structure of phosphate–vanadate hydroxyapatite [ 17 , 19 , 48 , 57 , 58 ].…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…In all recorded ATR-FT-IR spectra ( Figure 4 a–c), bands originating from the phosphate (PO 4 3− ), vanadate (VO 4 3− ) and hydroxyl (OH − ) groups are present. Their locations are consistent with the data available in the literature and confirm that the materials have the hexagonal structure of phosphate–vanadate hydroxyapatite [ 17 , 19 , 48 , 57 , 58 ].…”
Section: Resultssupporting
confidence: 88%
“…It can result in obtaining unique acid–base catalysts and highly active oxidation catalysts due to the Lewis acidic properties and appropriate redox potential of vanadium [ 17 ]. Due to the structural similarity of vanadate to phosphate, it can take over a regulatory function in cellular processes in which phosphate plays a key role [ 18 , 19 ]. This phenomenon is based on vanadate’s interaction with phosphate-dependent enzymes, i.e., phosphatases and kinases [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…4,6 Various studies of complete or partial isomorphous substitution of PO 4 3À by AsO 4 3À or VO 4 3À in the lattice of hydroxyapatite have been published. [7][8][9][10][11][12][13] Recently, we reported studies by UV, XRD, XPS, NMR and FTIR on the influence of the substitution degree x, on the local structure of the vanadate group in calcium phosphate and vanadate apatite solid solutions, Ca 10 (PO 4 ) 6Àx (VO 4 ) x (OH) 2 . 14 It was shown that the vanadate ions occupy the equivalent crystallographic sites of phosphate and that the presence of both phosphate and vanadate ions in the lattice led to high disorder of the structure accompanied with small changes in local symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…Mravcova ´et al 15 found that epiphyseal cartilage and the subperiosteous zone of the diaphysis accumulate V and that deposition of this metal is greatest in areas of recent bone formation and mineralization. It has also been reported that vanadate (VO 4 3À ) is incorporated into the HA lattice [Ca 10 (PO 4 ) 6 (OH) 2 ] replacing phosphate anions (PO 4 3À ) 10,81 and forming calcium vanadate apatite [Ca 10 (VO 4 ) 6 (OH) 2 ], 82 whereas, oxidovanadium(IV) (VO 2+ ) [vanadyl] is strongly adsorbed on the apatite lattice surface. 8 The incorporation of small quantities of VO 4 3À in the PO 4 3À sites has been highlighted to produce only slight distortions in the macroscopic and microscopic structure of the mineral phase of bones.…”
Section: Discussionmentioning
confidence: 99%